Disruption of Germination and Seedling Development in Brassica napus by Mutations Causing Severe Seed Hormonal Imbalance - Nguyen, Tung C. T.; Obermeier, Christian; Friedt, Wolfgang; Abrams, Suzanne R.; Snowdon, Rod J. (Frontiers in Plant Science, 2016)
The Brassica napus (oilseed rape) accession 1012-98 shows a disturbed germination phenotype that was thought to be associated with its lack of testa pigmentation and thin seed coat. Here we demonstrate that the disturbed germination and seedling development are actually due to independent mutations that disrupt the balance of hormone metabolites and their regulators in the seeds. High-throughput UPLC-MS/MS hormone profiling of seeds and seedlings before and after germination revealed that 1012-98 has a severely disturbed hormone balance with extremely atypical, excessive quantities of auxin and ABA metabolites. The resulting hypersensitivity to abscisic acid (ABA) and a corresponding increase in dormancy often results in death of the embryo after imbibition or high frequencies of disturbed, often lethal developmental phenotypes, resembling Arabidopsis mutants for the auxin regulatory factor gene ARF10 or the auxin-overproducing transgenic line iaaM-OX. Molecular cloning of Brassica ARF10 orthologues revealed four loci in normal B. napus, two derived from the Brassica A genome and two from the C genome. On the other hand, the phenotypic mutant 1012-98 exhibited amplification of C-genome BnaC.ARF10 copy number along with a chimeric allele originating from recombination between homoeologous A and C genome loci which lead to minor increase of Bna.ARF10 transcription on the critical timepoint for seed germination, the indirect regulator of ABI3, the germinative inhibitor. Bna.GH3.5 expression was upregulated to conjugate free auxin to IAA-asp between 2-6 DAS. Functional amino acid changes were also found in important DNA binding domains of one BnaC.ARF10 locus, suggesting that regulatory changes in Bna.ARF10 are collectively responsible for the observed phenotpyes in 1012-98. To our knowledge, this study is the ﬁrst to report disruption of germination and seedling development in Brassica napus caused by the crosstalk of auxin-ABA and the corresponding regulators Bna.ARF10 and Bna.GH3.5.